2017
DOI: 10.1016/j.cmet.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet Reduces Midlife Mortality and Improves Memory in Aging Mice

Abstract: Summary A ketogenic diet (KD) recapitulates certain metabolic aspects of dietary restriction such as reliance on fatty acid metabolism and production of ketone bodies. We investigated whether KD might, like dietary restriction, affect longevity and healthspan in C57BL/6 male mice. We find that an isoprotein KD, fed on alternate weeks to prevent obesity (Cyclic KD), reduces mid-life mortality but does not affect maximum lifespan. A non-ketogenic high-fat diet (HF) fed similarly may have an intermediate effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
328
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 397 publications
(355 citation statements)
references
References 41 publications
21
328
3
3
Order By: Relevance
“…A recent paper in which mice were fed a ketogenic diet did not show this daily rhythm despite having several health benefits (Roberts et al, 2017), implying that mechanisms underlying ketogenic and MF paradigms are different. Two recent studies indicated that mice on ketogenic diets exhibited either a weight gain and slight reduction in midlife mortality or a slight decrease in weight and increase in healthspan and lifespan (Newman et al, 2017; Roberts et al, 2017). Although ketogenic diets, when given in a paired feeding paradigm, extended lifespan, it is unclear whether periods of fasting may have been a contributing factor.…”
Section: Resultsmentioning
confidence: 99%
“…A recent paper in which mice were fed a ketogenic diet did not show this daily rhythm despite having several health benefits (Roberts et al, 2017), implying that mechanisms underlying ketogenic and MF paradigms are different. Two recent studies indicated that mice on ketogenic diets exhibited either a weight gain and slight reduction in midlife mortality or a slight decrease in weight and increase in healthspan and lifespan (Newman et al, 2017; Roberts et al, 2017). Although ketogenic diets, when given in a paired feeding paradigm, extended lifespan, it is unclear whether periods of fasting may have been a contributing factor.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has shown that ketogenic diet can improve the midlife mortality of mice and provide neurological benefits such as improved memory in aging mice. [ 82 ] The caloric restriction/anti‐aging mechanism of βHB has been ascribed to two overlapping mechanisms. i) in an energetic role, βHB provides an alternative (anaplerotic) source of carbon to the mitochondrial TCA cycle in the context of an aging‐associated mitochondrial dysfunction, ii) direct inhibition of HDAC I and IIa histone deacetylases (IC 50 ≈1 × 10 −3 m ) causing the deacetylation of FOXO3a promoter leading to transcriptional activation.…”
Section: Application Of Metabolomics For Biomarker Discovery In Agingmentioning
confidence: 99%
“…By themselves, ketone bodies also appear to target the metabolism and cardiac function via changes in nuclear transcription by acting as inhibitors of HDAC1, resulting in protection from oxidative stress (192). Mice fed ketogenic diets also show decreases in mTOR activity with increases in Sirt1 and HIF-1 as well as AMPK activity (145, 171). Besides states of nutritional deprivation, ketone bodies appear to play a significant role in cardiac metabolism in the post natal remodeling (43) as well as in models of heart failure (16, 22).…”
Section: Cardiac Energetics Substrate Metabolism and Pathophysiologymentioning
confidence: 99%
“…Besides states of nutritional deprivation, ketone bodies appear to play a significant role in cardiac metabolism in the post natal remodeling (43) as well as in models of heart failure (16, 22). Ketone bodies also drive acetylation reactions, which may explain its benefits on extending lifespan and improving healthspan seen when mice are maintained on a ketogenic diet chronically (171) or intermittently (145). In addition, among TCA cycle intermediates, oxaloacetate, and a-ketoglutarate appear to play roles outside their role in mitochondrial acetyl CoA/TCA metabolism.…”
Section: Cardiac Energetics Substrate Metabolism and Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation